Korelasi Kecerdasan Emosional dengan Perilaku Moral Remaja SMP di Desa Samirplapan Gresik - Eka Wahyu Hidayati (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2020)
A teenager is said to be intelligent in managing his emotions if he is able to accept, sympathize, motivate and control his personality with others around him. This study uses quantitative approach with questionnaire data collection techniques and documentation and then analyzed using product moment correlation. The objectives of this study are (a) to find out the emotional intelligence of junior high school adolescents in Samirplapan Village Sitsampeyan Gresik, (b) to find out the moral behavior of junior high school teenagers in Samirplapan Village, (c) to find out whether there is a correlation between emotional intelligence and moral behavior of junior high school students in Samirplapan village . The results of the product moment correlation test are known to count = 0.778> rtable = 0.334. Therefore it can be seen that there is a correlation between emotional intelligence with the moral behavior of adolescent junior high school in Samirplapan Duduksampeyan Gresik Village of 0.778 with a strong category. Based on these results, it can be concluded that the level of adolescent emotional intelligence is good, the moral behavior of adolescents is also good.